Analysis of the First 100 Patients From the Syrian Civil War Treated in an Israeli District Hospital. Issue 1 (January 2016) - Biswas, Seema; Waksman, Igor; Baron, Shay; Fuchs, David; Rechnitzer, Hagai; Dally, Najib; Kassis, Shokrey; Hadary, Amram
Abstract : Objective: An analysis of the injuries and treatment of the first 100 patients from the Syrian civil war was conducted to monitor quality of care and outcome. Summary Background Data: As reports of the collapse of health care systems in regions within Syria reach the media, patients find themselves crossing the border into Israel for the treatment of war injuries. Among these patients are combatants, noncombatants, women, and children. Treatment, that is free at the point of care, is a humanitarian imperative for war wounded, and this paper reports the care in an Israeli district hospital of the first 100 patients received. Methods: With ethics committee approval, data from the Trauma Registry and electronic patient records were collected and analyzed. No identifying data are presented. Results: Most patients (94) were male. Seventeen patients were younger than the age of 18 years; 52 patients were in their twenties. Most injuries were the results of gunshot or blast injury (50 and 29 patients, respectively). Two multiple-trauma patients died, 8 were transferred for specialist care, and 90 patients returned from Ziv Hospital to Syria after discharge. Conclusions: The experience of the care of patients across a hostile border has been unprecedented. Hospital protocols required adjustment to deliver quality clinical and social care to patients suffering from both the acute and chronic effects of civil war.